Conditional CRISPR-Cas genome editing in Drosophila to generate intestinal tumors - Bahuguna, Shivohum; Redhai, Siamak; Zhou, Jun; Wang, Tianyu; Port, Fillip; Boutros, Michael (Cells, 2021)
CRISPR-Cas has revolutionized genetics and extensive efforts have been made to enhance its editing efficiency by developing increasingly more elaborate tools. Here, we evaluate the CRISPR-Cas9 system in Drosophila melanogaster to assess its ability to induce stem cell-derived tumors in the intestine. We generated conditional tissue-specific CRISPR knockouts using different Cas9 expression vectors with guide RNAs targeting the BMP, Notch, and JNK pathways in intestinal progenitors such as stem cells (ISCs) and enteroblasts (EBs). Perturbing Notch and BMP signaling increased the proliferation of ISCs/EBs and resulted in the formation of intestinal tumors, albeit with different efficiencies. By assessing both the anterior and posterior regions of the midgut, we observed regional differences in ISC/EB proliferation and tumor formation upon mutagenesis. Surprisingly, high continuous expression of Cas9 in ISCs/EBs blocked age-dependent increase in ISCs/EBs proliferation and when combined with gRNAs targeting tumor suppressors, it prevented tumorigenesis. However, no such effects were seen when temporal parameters of Cas9 were adjusted to regulate its expression levels or with a genetically modified version, which expresses Cas9 at lower levels, suggesting that fine-tuning Cas9 expression is essential to avoid deleterious effects. Our findings suggest that modifications to Cas9 expression results in differences in editing efficiency and careful considerations are required when choosing reagents for CRISPR-Cas9 mutagenesis studies. In summary, Drosophila can serve as a powerful model for context-dependent CRISPR-Cas based perturbations and to test genome-editing systems in vivo.
Gesehen am 22.12.2021
This article belongs to the special issue "Research advances in invertebrate experimental models of malignant growth"